2016
DOI: 10.1111/1750-3841.13365
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Contents of Sugar, Amadori, and Heyns Compounds in Fresh and Black Garlic

Abstract: Black garlic is produced through thermal processing and is used as a healthy food throughout the world. Compared with fresh garlic, there are obvious changes in the color, taste, and biological functions of black garlic. To analyze and explain these changes, the contents of water-soluble sugars, fructan, and the key intermediate compounds (Heyns and Amadori) of the Maillard reaction in fresh raw garlic and black garlic were investigated, which were important to control and to evaluate the quality of black garl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 24 publications
7
57
0
3
Order By: Relevance
“…Choi et al (2014) [15] showed a 10-fold increase in reducing sugar content during 35 days of maturity stage. Yuan et al (2016) [16] observed an increase from 187.79% to 790.96%, explained mainly by changes in fructose and glucose content during the process, as black garlic showed similar sucrose concentration to fresh garlic. These considerable increases of fructose and glucose contents during black garlic production could be the result of the hydrolysis of fructans during the process, Yuan et al (2016) [16] observed a decrease of 84.6% of total fructans content in black garlic in relation to fresh garlic.…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al (2014) [15] showed a 10-fold increase in reducing sugar content during 35 days of maturity stage. Yuan et al (2016) [16] observed an increase from 187.79% to 790.96%, explained mainly by changes in fructose and glucose content during the process, as black garlic showed similar sucrose concentration to fresh garlic. These considerable increases of fructose and glucose contents during black garlic production could be the result of the hydrolysis of fructans during the process, Yuan et al (2016) [16] observed a decrease of 84.6% of total fructans content in black garlic in relation to fresh garlic.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, black garlic has attracted much attention as health‐oriented food product in the market because of better biological properties after fermentation, such as antioxidant, anticarcinogenic, and antihepatopathic activities (Bae and others ). After the thermal process, there was a decrease in fructan content, although there was an increase in total water‐soluble sugar content and Maillard reaction intermediates in black garlic (Yuan and others ). And it was indicated from previous reports that black garlic had stronger antioxidant activity than that of fresh garlic due to high amounts of organosulfur compounds (Jeong and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Black garlic can prevent the development of atherosclerosis by clearing cholesterol [8]. In black garlic, the content of allicin, which gives a harsh aroma taste, is reduced and allisin in the browning process is transformed into antioxidant compounds such as bioactive alkaloid and flavonoid compounds [9]. Black garlic have been consumed in extracted form as well as being used widely as an food ingredient including beverages, candy due to sour taste of it [10].…”
Section: Introductionmentioning
confidence: 99%